Sleeping behaviors of adolescents with depressive disorders: adolescent self-description of sleeping reported through a web-based support system - Anttila M; Kurki M; Valimaki M (TAYLOR & FRANCIS INC, 2022)
Background: Depression is the leading health disorder in adolescence and often manifests itself as sleeping problems. A number of quantitative analyses have assessed the quality of adolescents' sleeping, but there is still a lack of information on how adolescents themselves perceive their sleeping behavior. Method: Using a mixed-methods approach, we describe sleeping behaviors and sleeping habits among adolescents with depressive disorders, who have been referred to psychiatric outpatient services. Results: Adolescents monitored their own sleeping patterns (n = 13) and reported on them through self-reflecting writings (n = 16) on a web-based support system for one week. They went to bed to about 23:00, remained awake for around 40 minutes, slept eight and a half hours, woke up at 9:00, and described themselves as being tired after the night. Adolescents were able to self-reflect on their sleeping in various ways and find meanings and interpretations of it. Conclusion: The results contribute valuable information to health care personnel who work with adolescents, for example school nurses and mental health professionals. More emphasis should be put on adolescents' perceptions of their sleeping behavior and how to increase their insight into their own wellbeing.